(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Heterocyclic compounds are widely spread in nature and have diversified application in design of new drug molecule. This approach is used to design new antiepileptic agents. Based on various findings, one of the target protein for antiepileptic molecule is selective gamma amino butyric acid (GABA). Selective GABA is the controller of CNS activity. In this study, thiophene derivatives were used to design the new antiepileptic agents through a selective GABA activation. The probable activity of thiophene derivatives could be increased by substitution in all position of thiophene except 1st. Molecular docking of selective GABA activation was required to predict their antiepileptic activity. The molecular docking of thiophene analogues was carried out using AutoDock viva Ver.1.1.2. Twenty thiophene analogues were docked into GABAa with Protein data bank (PDB) code 4cof. The interaction was assessed based on the docking score. Diazepam was used as the standard for this study. Twenty thiophene analogues showed the approximate docking score -6.3 to -9.6 kcal/mol. Thirteen thiophene analogues which value that have greater docking score compared to diazepam used as a standard. Compound T-15 had higher binding energy than other thiophene analogue because it has the lowest docking score. All new thiophene analogues are possible to be synthesize and performed their pre-clinical evaluation.